Shear of rubber tube springs - Suh, J.B.; Gent, A.N.; Kelly, III, S.G. (International journal of non-linear mechanics, 2007)
Rubber tube springs consist basically of cylindrical rubber tubes bonded on their inner and outer curved surfaces to rigid cylindrical tubes. They are widely used as flexible linkages, for example in vehicle suspensions. Rotation of one rigid tube with respect to the other about their common axis subjects the rubber tube to azimuthal shear. Displacement of one rigid tube with respect to the other along their common axis puts the rubber tube into axial shear. Using FEA, we have calculated the stresses set up in both cases, for a long rubber tube of a non-linearly elastic (neo-Hookean) material. The results are compared for the two modes of deformation, and with analytical predictions where available. For a long tube the shear stresses are substantially independent of the end conditions, but the normal stresses are strongly affected, as found previously for sheared rectangular blocks [A.N. Gent, J.B. Suh, S.G. Kelly III, Mechanics of rubber shear springs, Int. J. Nonlinear Mech. 42 (2007) 241–249]. If the end surfaces are stress-free, unexpectedly large normal stresses are generated, even in azimuthal shear. These high tensile stresses are attributed to restraints at the inner and outer cylindrical boundaries that compensate for the absence of stresses on the end surfaces that would be needed to maintain a simple shear deformation. Thus, the boundary conditions affect the stresses everywhere (in contrast to an “end effect” that would diminish away from the ends). Small departures from complete incompressibility are found to lower the internal stresses markedly, and even cause the sign of the stresses to be reversed.